'When it faded in her … it faded in me': a qualitative study exploring the impact of care-giving on the experience of spousal intimacy for older male care-givers. Issue 1 (13th January 2021) - Fee, Anne; McIlfatrick, Sonja; Ryan, Assumpta
Abstract: Older male care-givers play an increasingly important role in informal care-giving, yet they have received little attention in the literature. The aim of this study was to explore the impact of care-giving on the experience of spousal intimacy for older male care-givers. Twenty-four older male care-givers, drawn from a region of the United Kingdom, participated in one-to-one interviews about their care-giving role. Thematic analysis was used to analyse data, and the study was underpinned by theories of masculinity. Three main themes were identified: (a) 'Impact of care-giving on the experience of sexual intimacy'; (b) 'Impact of care-giving on the experience of emotional intimacy'; and (c) 'Not up for discussion'. When sexual intimacy declined, some older male care-givers prioritised emotional intimacy; some struggled with the decline; and some were reluctant to discuss the issue. Additionally, some care-givers reported that they had not received support from external support providers for declining sexual or emotional intimacy. Intimacy has been highlighted as important for care-givers given its link with care-giver wellbeing and quality of life. Results of this study suggest that sexual and emotional intimacy was an issue for older male care-givers, and that this issue should be considered by external support providers as part of a holistic assessment of need in order to tailor effective support.